1998
DOI: 10.1007/s004280050215
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human papillomaviruses in squamous cell carcinomas of the lung

Abstract: The aim of this study was to evaluate the possible association of human papillomaviruses (HPV) with the development of squamous cell lung carcinomas (SqCLCs). Tissue material from 52 cases of SqCLCs were studied, and the data were evaluated according to the degree of differentiation, HPV presence and type. Analysis was performed by polymerase chain reaction (PCR) method using consensus primers, and the results were confirmed by subsequent Southern blot hybridization. Overall, the results showed 69% positivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 39 publications
4
18
0
Order By: Relevance
“…A Greek study also showed such an association (Papadopoulou et al, 1998). We also observed pearl formation in 4 out of 8 well-differentiated SQCs (50%).…”
Section: Discussionsupporting
confidence: 78%
“…A Greek study also showed such an association (Papadopoulou et al, 1998). We also observed pearl formation in 4 out of 8 well-differentiated SQCs (50%).…”
Section: Discussionsupporting
confidence: 78%
“…High and low incidence regions are found in southern and northern European countries alike. In particular, the two studies from Athens, one reporting 0% and the other 69% are confusing [33,34]. They can neither be explained by the cancer type (both analyzed SCC, in one study also ADC and LCLC were investigated), material (both used frozen and FFPE samples) or the methodology (both studies used PCR, once in conjunction with a Southern blot technique while the other additionally applied in situ hybridization).…”
Section: Discussionmentioning
confidence: 92%
“…Diagnosis of various infectious diseases can be efficiently supported by the application of molecular analysis [3,13,18]. For specific detection of mycobacterial DNA, amplification of the ribosomal 16S rRNA-fragment gene [6,11], the 65-kDa antigen gene [21,22], the insertion fragment IS986/6110 [4,19] and the fragment MTP40 [8,10] have proved useful.…”
Section: Introductionmentioning
confidence: 99%